Probing the axion-nucleon coupling with the next generation of axion helioscopes - Di Luzio, Luca; Galan, Javier; Giannotti, Maurizio; Irastorza, I.; Jaeckel, Joerg; Lindner, Axel; Ruz, Jaime; Schneekloth, Uwe; Sohl, Lukas; Thormaehlen, Lennert J.; Vogel, Julia K. (The European physical journal. C, Particles and fields, 2022)
A finite axion-nucleon coupling, nearly unavoidable for QCD axions, leads to the production of axions via the thermal excitation and subsequent de-excitation of $$^{57}$$Fe isotopes in the sun. We revise the solar bound on this flux adopting the up to date emission rate, and investigate the sensitivity of the proposed International Axion Observatory IAXO and its intermediate stage BabyIAXO to detect these axions. We compare different realistic experimental options and discuss the model dependence of the signal. Already BabyIAXO has sensitivity far beyond previous solar axion searches via the nucleon coupling and IAXO can improve on this by more than an order of magnitude.